Evading Frames: D’Antin van Rooten’s Homophonic Mother Goose - Fraser, Ryan (TTR)

(untitled) (Association canadienne de traductologie, 2012)
In 1967, American dialect actor Luis d’Antin van Rooten published his now-classic Mots d’Heures: Gousses, Rames, a non-organic arrangement of French-language words and phrases designed to approximate the speech sounds of Mother Goose Rhymes. Though much read and imitated, these homophonic translations have largely evaded theoretical focus. Perhaps this is because their unique structuring allows them to evade anchorage in any specific contextual frame, and to send up the researcher’s own efforts toward contextualization, which has been prescribed as the methodological “first step” in Translation Studies since the Cultural Turn. Presented here, first of all, is a search for the potential frames of the Mots d’Heures–biographical, inter-textual, cinematic. These homophonic translations, I will then contend with reference to Jean-Jacques Lecercle (1990), exist to defy these frames by collapsing together, at the phono-articulate level, the target text with its most obvious context: the English-language source. Finally, I would contend, this collapse exemplifies the phenomena of “weaning,” “trans-contextual drift,” and “remainder” argued by Derrida (1988) as the enduring property of the signifying structure. The Mots d’Heures serve, then, as a playful reminder, in an intellectual climate where context reigns, of the signifying form’s structural ascendancy over the frame, of its “iterability.”